Racial and Ethnic Disparities in Diabetes Prevention Outcomes: Insights from the Prediabetes Informed Decisions and Education Study - Yelba Castellon-Lopez; O. Kenrik Duru; Norman Turk; Gerardo Moreno; Keith C. Norris; Amanda Vu; Rintu P. Saju; Chi-Hong Tseng; Kia Skrine-Jeffers; Carol M. Mangione; Dominick Frosch; Tannaz Moin (Health Equity)
Background: To achieve health equity, interventions should yield similar effectiveness across all patient subgroups. However, the adoption of diabetes prevention strategies and successful weight loss in “real-world” Diabetes Prevention Program (DPP) translational studies have varied by race and ethnicity. We examined racial and ethnic differences in diabetes prevention outcomes among study participants from the Prediabetes Informed Decisions and Education (PRIDE) Study. Methods: In a retrospective analysis of data from the PRIDE cluster randomized trial across a large health system, we examined (1) percent weight change and (2) uptake of DPP and/or metformin among overweight/obese participants with prediabetes 12 months after participating in a pharmacist-led shared decision-making (SDM) intervention. We stratified the outcomes by race and ethnicity using a generalized linear mixed-effects model. Results: The study participants (n = 515) had an average age of 56 years (standard deviation [SD] = 11.0), hemoglobin A1c of 6.0% (SD = 0.20), and body mass index of 30.3 (SD = 5.2). Black/African American and Latino study participants lost significantly less weight at the 12-month follow-up compared with White/Caucasian participants (−1.0% and −1.2%, respectively, vs. −3.3%, p < 0.01 for both comparisons). There was no significant difference in the adoption of diabetes prevention strategies between racial and ethnic groups after completing an educational SDM intervention. Conclusion: To better promote health equity, future studies should investigate the potential causal factors for these differences in weight loss, such as variations in socioeconomic status, physical activity, cultural influences, and neighborhood characteristics.